Problems of Staffing for the Scientific and Technological Development of Russia in the Light of the New Education Development Strategy Formation until 2040 - E. V. Karavaeva; V. V. Malandin (Высшее образование в России)
The new global challenges facing the Russian Federation in recent years have raised the demand for technological leadership and the transition to a model of sustainable scientific and technological development to an unprecedented high level. The professional education of highly and highly qualified researchers and developers takes the special place in overcoming these challenges. Being directly involved in the development of the Strategy of Education development until 2040, the authors note that the developers clearly underestimate the depth of the problem of staffing Russian science and the need for a systematic solution to issues related to the training of scientific and scientific-pedagogical personnel in graduate school. This paper is devoted to the analysis of open data on the state of human resources in Russian science and the effectiveness of postgraduate programs, as well as to the discussion of several proposed “innovations” in the implementation of postgraduate programs in the new national education system.